Comparison of Business Model Canvas (BMC) among the three consulting companies - Azhar Amanullah, Ayn Nur Azhana; Ab Aziz, Nur Faizah; Abd Hadi, Nurafiqah Hanis; Ibrahim, Jamaludin (Research Publish Journals, 2015)
The Business Model Canvas (BMC) helps the companies in creating their business models based on nine building blocks. BMC is a tool that provides a clear view of what the company needs to achieve and focuses on the strategic elements that matter most and will have the greatest impact to the business. In this paper, we discuss on three consulting companies: ITECH Consulting, Kincardin Group, and Glen Ford’s Project Management Consultant. These three companies are then compared among the nine building blocks in the BMC and we focused on key resources, value proposition, and customer segments in order to identify which BMC is the best among those three companies.